Pirate treasure hunt! - Peck, Jan (Pelican Pub., 2008)
Captain Dare and his newly hired mates set out in search of treasure, swimming through a lagoon, swinging through a jungle, and other obstacles before finding the treasure, until a mouse frightens the Captain into retreat.